Analysis on Patents of Hot Dip Plating Technology for Steel Structure - YUE Zeng-wu, ZHANG Zhen-yue, LI Xiao-yu, MA Yong-quan, SHAO Ming-xing (Cailiao Baohu, 2021)
Hot dip plating is one of the most widely used technologies for steel structure corrosion protection. Based on the CPRS, WPI DII and the WORDWIDE, the related patents technologies of hot dip plating were retrieved. Hot dip plating patents were analyzed based on four aspects-patent application situation, regional distribution, patent applicants and technology branches. The gaps between China and other countries on patent application were pointed out, which would provide some guidance on the industry development and patent application technique.